PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN KANTOR PT. KERETA API INDONESIA (PERSERO) DAOP IV SEMARANG - Putri Rizqy; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
Employee performance is an important thing that should be considered to create quality human resources to achieve corporate goals. There are several factors that affect the performance of employees that is work environment, work discipline and compensation. PT. Kereta Api Indonesia (Persero) is a state corporation that is engaged in transportation, especialy train. In the last four quarters of PT. KAI DAOP IV Semarang work discipline decline followed by a decline in profit. The purpose of this study was to determine the effect of the work environment, work discipline and compensation to employees performance of the office in PT. KAI DAOP IV Semarang. The study uses a quantitative approach. The sampling method selected is proportional sample as many as 112 people. The results showed that the work environment positive effect on the performance of 7.4%, work discipline positive effect on the performance of 23.1% and a positive influence on the compensation performance of 13.8%. Simultaneously work environment, work discipline and compensation positive effect on the performance of 32.3%. Suggestions for companies are more disciplined employees so that employees have a high awareness of the rules, the duties and responsibilities of employees in the work to improve performance.